Comparison of midlife offspring cohorts based on family history of Alzheimer's Disease: multi‐domain risk factors and cognitive function. (20th December 2022) - Zhang, Xuan; Mbangdadji, Djass; Li, Zhiguang; Sigurdsson, Sigurdur; Gudnason, Vilmundur; Meirelles, Osorio; Launer, Lenore J.
Abstract: Background: Maintaining healthy clinical indicators and behavior is positively related to cognitive protection from midlife. However, limited population‐based studies have explored the role of family history on these factors in midlife. Therefore, we examined cognitive‐related risk factors in two midlife cohorts from the same source population in the Age, Gene/Environment Susceptibility‐Reykjavik Study. Method: We included 446 offspring (aged 61, 49% women) from the random sample (RS) without Alzheimer's Disease (AD) and 499 offspring (aged 63, 49% women) to AD cases at baseline and during follow up from the main study. Accordingly, we labeled the offspring with and without AD family history as offspring AD and offspring RS, respectively. Clinical factors included BMI, systolic (SBP) and diastolic blood pressure (DBP), cholesterol, fasting glucose, inflammatory factors, and medication. Socio‐behavioral factors included education, smoking, problems of doing usual activities. Cognitive function was evaluated by MMSE and STROOP. To address the potential correlation between siblings within one family, we compared these characteristics with the random effects intercept mixed model by family ID. We also did a sensitivity analysis by comparing people under age 65 to assess reverse causation for specific traits. All models were adjusted for age and sex. Fasting glucose, triglycerides, and inflammatory factors were log‐transformed due to skewness. We consider p<0.05 as statistically significant. Result: As shown in the table, socio‐behavioral factors, cognitive function, or most clinical characteristics did not differ in the two groups. The Offspring AD had 2.71‐unit lower SBP and 0.03‐unit higher log(glucose) (3% increased glucose) than the RS (p<0.05). The sensitivity analysis among people under age 65 showed a similar pattern, except for the insignificant difference in fasting glucose between offspring AD and RS. Conclusion: In general, there was no difference in AD‐related health profile among midlife offspring with and without AD family history. This analysis of standard cardiovascular and cognitive impairment‐related risk factors suggests that these variables alone will not help identify at‐risk individuals for later‐life cognitive impairment.